Current typologies of social workers in Spain - Viscarret Garro, Juan Jesús; Ballestero Izquierdo, Alberto; Idareta Goldaracena, Francisco; Úriz Pemán, María Jesús (Cuadernos de Trabajo Social, 2016)
The aim of the article is to define and explain the current types of social work professionals in Spain, through descriptive, quantitative and typological research. This first investigation may help to instigate reflection on the professional organization of social work in Spain and to identify the features that define work in the profession. The results reveal the existence of twelve types of social work professionals in Spain.